Liquid metal battery storage in an offshore wind turbine: Concept and economic analysis. (October 2021) - Simpson, J.G.; Hanrahan, G.; Loth, E.; Koenig, G.M.; Sadoway, D.R.
Abstract: As wind energy increases its global share of the electrical grid, the intermittency of wind becomes more problematic. To address the resulting mismatch between wind generation and grid demand, long-duration (day-long) low-cost energy storage is offered as a potential solution. Lithium-ion (Li-ion) storage is an obvious, well-developed candidate, but it is currently too expensive for such long-duration applications. Liquid metal battery (LMB) storage offers large cost reductions and recent technology developments indicate it may be viable for MW-scale storage. Accordingly, we investigate co-locating and integrating LMB and Li-ion storage within the substructure of an offshore wind turbine. Integration allows the substructure to cost-effectively double as a storage container and allows for costly electrical farm-to-shore connections to be reduced to near the average power size (by reducing peak power). These benefits are compared to the costs for battery integration. Simulations show that line size can be reduced by 20% with 4 h of storage or by 40% with 12 h of storage, with negligible capacity factor losses. However, with 24 h of average power storage using LMB, no line size reduction provided the best overall net value of the turbine-storage system due to the ability to capture all available wind energy and profit from energy arbitrage and full capacity credit. In general, LMB integrated storage results in an increased relative value with current system costs. Projected technology trends indicate that these benefits will significantly improve and that integrated Li-ion storage will also become cost-effective. Graphical abstract: Image 1 Highlights: Low-cost, long-duration energy storage is needed for renewable energy integration. Liquid metal battery storage may be preferred option over Li-ion storage. Integrating battery directly into offshore wind turbine has potential cost savings. Electrical line sizes can be reduced by 20% with 4 h of storage capacity. Simulations of offshore wind turbine integrated with storage indicate net benefit.